Pengendalian Kualitas Produk Rak Display Guna Mengurangi Cacat di UD. Afareza Rajarak - Ansori, Mhammad Zain Al; Khoiroh, Siti Muhimatul (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
UD Afareza Rajarak is an industrial engaged in manufacturing and retail trade that produces racks. Two types of products are often ordered by customers, namely wall shelves and wicket racks. There are 4 product defects such as imprecise transverse wire, bent hollow iron, bent transverse wire, and poor welding residue. The highest percentage of defects for wall rack products was 4.81% in January 2024 and wicket racks were 5.05% in December 2023. Causing turnover losses to UD. Afareza Rajarak annually, with the largest loss in December amounting to Rp 3,956,250. This study aims to determine the factors that cause defects and how to reduce product defects in UD. Afareza Rajarak uses the Plan Do Check Act (PDCA) and Failure Mode and Effects Analysis (FMEA) methods. The factors causing damage are human factors, methods, machines, raw materials, and the environment. Apply fixes based on PDCA methods that have been performed. Keywords: Quality, Product, Defective, PDCA, FMEA